New high-resolution prototype versus standard spectralis optical coherence tomography in patients with central serous chorioretinopathy - Lorenzo Ferro Desideri; Luc Hennebert; Yousif Subhi; Martin Zinkernagel; Rodrigo Anguita (International Journal of Retina and Vitreous)
Abstract Purpose To assess the accuracy of High-Resolution OCT in detecting biomarkers associated with central serous chorioretinopathy (CSC) compared to standard OCT. Methods We conducted a cross-sectional study involving CSC patients who underwent High-Resolution and standard OCT during the same visit. Using the SPECTRALIS High-Res OCT device (Heidelberg Engineering, Heidelberg, Germany), macular B-scans were obtained and compared with those acquired using a SPECTRALIS HRA + OCT device (Heidelberg Engineering, Heidelberg, Germany). Qualitative assessments were performed, and statistical analyses compared the performance of both OCT modalities. Results Thirty-one patients diagnosed with CSC were included with a mean age of 56.3 years (± 10.2). Among them, 29% (n = 9) were classified as acute CSC (aCSC), while 71% (n = 22) had chronic CSC (cCSC). High-Resolution OCT outperformed standard OCT in detecting microstructural changes in the outer retinal layers, including a higher prevalence of disrupted interdigitation zone (IZ) (29% vs. 6%, p = 0.003) and retinal pigment epithelium (RPE) disruption (12% vs. 2%, p = 0.0024). Intergrader agreement was high (Cohen’s Kappa = 0.85). Conclusion High-Resolution OCT demonstrates promise in identifying critical biomarkers associated with CSC, particularly disruptions in the IZ and RPE. Further validation in larger cohorts is required to confirm their clinical relevance in patients with CSC.